2012
DOI: 10.1088/0957-4484/23/47/475703
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of ZnO nanoparticles with a modified surface under ambient illumination

Abstract: In various practical applications, nanomaterials typically have functionalized surfaces. Yet, the studies of toxicity and antibacterial activity of functionalized nanoparticles are scarce. We investigated the effect of surface modifications on antibacterial activity of ZnO under ambient illumination, and we found that nanoparticles coated with different surface modifying reagents could exhibit higher or lower toxicity compared to bare ZnO, depending on the surface modifying reagent used. Different surface mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 67 publications
1
92
2
Order By: Relevance
“…11. All samples exhibit absorption peaks at $3420 cm À1 and 1626 cm À1 attributed to the vibration modes of OH groups and scissoring mode of molecular water, respectively [54][55][56][57]. The small peaks at 2924 cm À1 and 2855 cm À1 correspond to C-H bond from organic materials adsorbed on the surface.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…11. All samples exhibit absorption peaks at $3420 cm À1 and 1626 cm À1 attributed to the vibration modes of OH groups and scissoring mode of molecular water, respectively [54][55][56][57]. The small peaks at 2924 cm À1 and 2855 cm À1 correspond to C-H bond from organic materials adsorbed on the surface.…”
Section: Resultsmentioning
confidence: 97%
“…This possibly indicates lower presence of adsorbed OH groups in this sample, which could affect its toxicity. For 1-CeO 2 and HT-CeO 2 there are absorption peaks near 1560 cm À1 and 1384 cm À1 which arise from the antisymmetric stretching band of carboxyl group and absorption of CO 2 on the metallic cations, respectively [54,57]. The more numerous and pronounced peaks associated with organic molecules on 1-CeO 2 and HT-CeO 2 indicate either the presence of adsorbed surfactant molecules or the unintentional residues introduced from the synthesis procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Abd Gani et al (2014) showed that coating TiO 2 particles with fatty acids commonly used in cosmetics can increase UV absorption, but have not demonstrated the efficacy of "nanosized" particles. Leung et al (2012) observed that the antibacterial activity is enhanced as a result of surface modification of zinc oxide NPs. However, neither study examined the effect of surface modification of NPs in cell toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of ROS has been known to contribute to ZnO NPs antibacterial activity [31]. In this study, radical scavengers (Mannitol, Vitamin E and Glutathione (GSH)) were employed to indirectly assess whether radical formation was responsible, , because they can alter the kinetic profile of the reaction.…”
Section: Possible Antibacterial Mechanism Of the Generation Of Reactimentioning
confidence: 99%